My Smart Speaker is Cool! Perceived Coolness, Perceived Values, and Users' Attitude toward Smart Speakers. Issue 6 (3rd April 2021) - Ashfaq, Muhammad; Yun, Jiang; Yu, Shubin
ABSTRACT: Although smart speakers are widely accepted by consumers today, especially in developed countries such as the United States (US), few marketing-focused empirical studies on smart speakers have been conducted. To address this gap in the literature, the current study aims to explore the effects of perceived coolness on consumers' attitudes toward smart speakers through perceived values (i.e., functional, hedonic, economic, and social value). Data were collected from the current smart speaker users in the US using an online questionnaire. The study employed partial least squares structural equation modeling (PLS-SEM) approach on 307 validated responses. The SEM analysis showed that perceived coolness, which consisted of four dimensions: perceived functionality, attractiveness, subcultural appeal, and originality, had a positive effect on the functional, hedonic, economic, and social value. The findings further revealed that consumers' attitude toward smart speakers was influenced by functional, hedonic, and economic value, but not by social value. Additionally, the attitude was found to be a strong predictor of continuance intention. This study is one of the early attempts to explore the current smart speaker users' attitudes and their intentions to continue using AI-based voice assistants' devices.